Menggali Konsep Belajar dalam Islam - Rusuli, Izzatur (Ta'dib: Jurnal Pemikiran Pendidikan, 2024)
Learning is a fundamental need for humans to enhance their quality of life. Islam places great importance on learning and has its unique concepts regarding it. This study aims to comprehensively explore the concept of learning in Islam, including its definition, the virtues of learning, the objectives of learning, the ethics of learning, the principles of learning, and the factors influencing learning success. This is a qualitative research study utilizing a literature review approach. The data analysis technique used in this research is content analysis. The results show that learning is a process of seeking knowledge and then applying it to become a perfect human being. A Muslim individual who seeks knowledge in Islam is granted the virtues of being elevated in rank, facilitated in the path to paradise, and prayed for. The objective of learning in Islam is to draw closer to Allah. The ethics of learning in Islam involve paying attention to one's intentions, being earnest, avoiding laziness, recognizing one's abilities, and having aspirations. Islam also outlines principles of learning, including intention (niyyah), motivation (al-hathth), gradual progression (tadarruj), reward (thawab), repetition (takrir), focus (tarkiz), attention (ihtimam), active participation, and time management. Factors influencing learning success include a heart purified from sins and piety. In conclusion, learning in Islam is not limited to worldly matters but also greatly emphasizes the spiritual aspect.